Analysis of the Implementation of Information Processing Models in Learning at SMA Negeri 3 Banjar - Muhammad Rakha Fauzan; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education continues to evolve alongside the changing dynamics of information and technology, influencing the patterns of learning. Amidst these changes, the theory of information processing emerges as a critical concept in understanding and designing effective learning experiences. Information processing involves a series of mental processes that encompass reception, comprehension, storage, and utilization of received information. This research aims to analyze the implementation of the information processing model in the context of learning at SMA Negeri 3 Banjar. Through a qualitative approach involving literature review and field observations, the research findings indicate that the learning activities at SMA Negeri 3 Banjar have successfully integrated components of the information processing model. The learning process includes relevant stages, indicating the success and effectiveness of implementing this model in the educational environment of SMA Negeri 3 Banjar. These findings provide valuable insights into the relevance of the information processing model in enhancing the quality of education in this institution.